The Influence of Motivation, Entrepreneurship Education, Family Environment, and Capital on Student Entrepreneurial Interests in East Java - Rizal Ula Ananta Fauzi; Afrista Maratul Aqidah (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
This study aims to determine the effect of Motivation, Entrepreneurship Education, Family Environment and Capital on Students' Interest in Entrepreneurship in East Java. The sample in this study was taken using purposive sampling, in order to obtain 350 samples. The data analysis technique used descriptive statistics, path diagram development, measurement model (outer model), structural model (inner model) and hypothesis testing. Based on the data analysis, it can be concluded that motivation affects interest in entrepreneurship, entrepreneurship education affects interest in entrepreneurship, family environment does not affect interest in entrepreneurship, and capital does not affect interest in entrepreneurship.